ROLE OF SOCIAL SUPPORT GROUP IN PROMOTING OR PREVENTING DEPRESSION AND REMEDIES TO MINIMIZATION OF THE DEPRESSION PROBLEM FOR STUDENTS AND PARENTS - Gupta , Nishi; Kumar Srivastava, Ashok (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social support has been demonstrated to be useful in enhancing mental health by acting as a cushion against stressful life conditions. Social support originates from a network of individuals comprising friends, family, and the community. Lack of social support worsens students’ mental health issues, particularly signs of depression, and affects their quality of life. A multifaceted strategy is essential to mitigate depression among students and parents, emphasizing prevention, early intervention, and support. This encompasses the promotion of healthy habits, the encouragement of open communication, and the pursuit of expert assistance as required. Students and parents can enhance resilience by practicing self-care, obtaining support from peers and trustworthy adults, and participating in activities that foster joy and purpose. In this article, role of social support group in promoting or preventing depression and remedies to minimization of the depression problem for students and parents has been discussed.